Systematics, Bioecology, and Medical Importance of Widow Spiders (Lathrodectus spp.) in Khorasan Province, Iran - J Rafijenad; S Tirgari; F Biglarian; K Shemshad (Journal of Arthropod-Borne Diseases, 2007)
Following the hospitalization of 195 individuals due to the spider bite in 1995 and three cases of recorded death in the year of 1993 which were referred to Emam Reza Hospital in Mashad, the present study was undertaken on bionomics and medical importance of Lathrodectus spp in Khorasan Province, during 1995-2005. A total cases of 195 bites were studied composing of 70.8 % males and 29.2% females. The most prevalence cases were observed in mid age (20-55 years old) and par¬ticularly among farmers (36.4%). A total number of 216 adult widow spiders and 258 egg sacs were collected from their habitats in different localities of 15 counties in the province. The following species have been recognized: Lathrodectus tredecimgottatus (62%), L. dahli (32%), L. geometricus (5%) and L. pallidus (1%). Here is the first report on the occurrence of males of L. pallidus as well as both sexes of L. trdecimgottatus and L. geometricus in the country. The sex ratio among collected specimens was 88% and 12% female and male, respectively. Summer provides the most suitable and favorable climatic condition for the activities of these spiders. However 65% of spiders were collected in this season. Among different cit¬ies, Mashad had (60%) the most reported cases in the study area. Foot was more injured than other parts. 96.5% of pa¬tients exhib¬ited localized pain from which only 2% had no pain in the bitten part and 87% had a generalized pain in whole body.